Understanding the Role of Past Health Care Discrimination in Help-Seeking and Shared Decision-Making for Depression Treatment Preferences. (October 2020) - Progovac, Ana M.; Cortés, Dharma E.; Chambers, Valeria; Delman, Jonathan; Delman, Deborah; McCormick, Danny; Lee, Esther; De Castro, Selma; Sánchez Román, María José; Kaushal, Natasha A.; Creedon, Timothy B.; Sonik, Rajan A.; et al.
As a part of a larger, mixed-methods research study, we conducted semi-structured interviews with 21 adults with depressive symptoms to understand the role that past health care discrimination plays in shaping help-seeking for depression treatment and receiving preferred treatment modalities. We recruited to achieve heterogeneity of racial/ethnic backgrounds and history of health care discrimination in our participant sample. Participants were Hispanic/Latino ( n = 4), non-Hispanic/Latino Black ( n = 8), or non-Hispanic/Latino White ( n = 9). Twelve reported health care discrimination due to race/ethnicity, language, perceived social class, and/or mental health diagnosis. Health care discrimination exacerbated barriers to initiating and continuing depression treatment among patients from diverse backgrounds or with stigmatized mental health conditions. Treatment preferences emerged as fluid and shaped by shared decisions made within a trustworthy patient–provider relationship. However, patients who had experienced health care discrimination faced greater challenges to forming trusting relationships with providers and thus engaging in shared decision-making processes.